A protocol to determine seed storage behaviour - Hong, T.D.; Ellis, R.H.; International Plant Genetic Resources Institute (1996)
This publications provides an approach by which conservationists can determine whether or not long-term seed storage is feasible for a particular species, i.e. whether or not that species shows orthodox seed storage behaviour. It provides advice on the implementation of the protocol, examples of ways in which the results from seed storage studies could be misinterpreted due to confounding factors, as well as several alternative approaches for estimating seed storage behaviour prior to carrying out actual investigations with the seeds. In particular, the latter section introduces the concept of a multicriteria approach for estimating seed storage behaviour. It is intended to be used along with the Compendium (see IPGRI Handbooks for Genebanks No.4 - Seed Storage behaviour: a Compendium); these two publications are essentially complementary. The overall aim of the protocol is to guide and encourage further work in this area of seed physiology (particularly for species on which relatively less work has been done to date)m with the objective to expanding on/up-dating the type of species-specific data compiled in the compendium.